2023
DOI: 10.1371/journal.pone.0281244
|View full text |Cite
|
Sign up to set email alerts
|

Equity incentive contract characteristics and company operational performance—An empirical study of Chinese listed companies

Abstract: Equity incentive, as an institutional arrangement for the coordination of the interests of shareholders and managers, has been widely implemented by public companies in developed capital markets throughout Europe and America. However, does it work and/or when might it be more effective in emerging market economies such as China? We aimed to understand the effects of equity incentive plans implemented by listed companies in China and the potential influence of the general characteristics of contracts on the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
(74 reference statements)
0
5
0
Order By: Relevance
“…In today's competitive service industry, the pressure to boost productivity, cut costs, and improve service quality is immense. Qin-Xia [12].With the rapid development of B&B, it is necessary to understand the factors influencing their density and type distribution at the micro scale [13]. The influence of the Internet on our social and economic life is well documented [14].…”
Section: Methodsmentioning
confidence: 99%
“…In today's competitive service industry, the pressure to boost productivity, cut costs, and improve service quality is immense. Qin-Xia [12].With the rapid development of B&B, it is necessary to understand the factors influencing their density and type distribution at the micro scale [13]. The influence of the Internet on our social and economic life is well documented [14].…”
Section: Methodsmentioning
confidence: 99%
“…By incentivizing executives, animal husbandry enterprises can closely combine the interests of executives with the interests of enterprises and shareholders, so that the goal of executives for enterprise development will change from pursuing short-term profit maximization to pursuing the maximization of corporate value in order to actively increase R&D investment and promote the improvement of the TFP of enterprises. Common incentive methods for the listed companies to corporate executives include equity incentives and compensation incentives [44]. In terms of equity incentives, the acquisition of equity by an executive makes the executive one of the owners of the business [45,46].…”
Section: The Moderating Effect Of Executive Incentives In the Impact ...mentioning
confidence: 99%
“…They are also believed to foster green innovation and ultimately bolster corporate performance (Yin et al, 2021). Qiao et al (2023), utilizing a multiple linear regression model on samples of equity incentive plans rolled out in China from 2010 to 2018, noted that the operational performance of companies post-implementation of these equity incentive plans exhibited a polarized trend. Both Erickson et al (2006) and Zhang et al (2022) identified a potential downside, observing that equity incentives might amplify a company's earnings management behavior.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They are also believed to foster green innovation (Wu et al ., 2022) and ultimately bolster corporate performance (Yin et al ., 2021). Qiao et al . (2023), utilizing a multiple linear regression model on samples of equity incentive plans rolled out in China from 2010 to 2018, noted that the operational performance of companies post-implementation of these equity incentive plans exhibited a polarized trend.…”
Section: Literature Reviewmentioning
confidence: 99%